Analysis and Characterization of Shielding Material for Mitigating Electromagnetic Interference in UAVs - Yanuar Prabowo; Imas Tri Setyadewi; Mohammad Amanta Kumala Sakti; Yomi Guno; Wahyudi; Donatina Miswati Hadiyanti; Novelita Rahayu; Nurul Lailatul Muzayadah; Cahya Edi Santosa (LPPM Universitas Negeri Semarang, 2025)
This study aims to mitigate the impact of electromagnetic interference on the performance of electronic systems in Unmanned Aerial Vehicles (UAVs) by employing various shielding materials. The materials tested include carbon fiber, E-glass, E-glass with an aluminium foil, and E-glass with a copper foil. A Vector Network Analyzer (VNA) and scattering parameter (S-Parameter) analysis, including reflection, absorption, and multiple reflection, were used to evaluate the shielding effectiveness of these materials within the frequency range of 4 - 5 GHz. The results showed that E-glass coated with copper had good overall shielding performance for SER, SEA, and SET values. This material reached a SET value of 96 dB at a frequency of 4.6 GHz, followed by E-glass coated with aluminium. In addition, adding carbon layers increased the shielding effectiveness, while E-glass without coating had the lowest shielding performance compared to the other materials. These findings indicate that E-glass coated with metal provides superior shielding effectiveness compared to carbon fiber, even when used in greater thickness.